Modeling company failure: a longitudinal study of Turkish banks - ÇİNKO, MURAT (TAYLOR & FRANCIS LTD, 2014)
Determining the factors related to the financial failure of a company is important. In this paper, we extend literature on bank failure prediction by modelling bank failures in Turkey from 1998 to 2000 using three statistical models combined with a principal component analysis on financial ratios. The three statistical models employed are a logistic regression, a logistic regression that takes serial correlation into account via generalized estimating equations and a marginalized transition model (MTM). Time and financial ratios that are related with capital adequacy and profitability, risk, non-interest income and Fx assets to Fx liabilities are found to be significant in classifying failed banks. Each of our methods achieves a correct classification rate of 93.3%. Among the three models, MTM, which is the soundest model in terms of statistical assumptions, shows slightly better model fit properties.
Keywords: uncertainty modelling; regression; financial ratios; hierarchical models; panel data; MARGINALIZED TRANSITION MODELS; SEMIPARAMETRIC REGRESSION; REPEATED OUTCOMES; FINANCIAL RATIOS; PREDICTION